A redefinition of Dorythrips (Thysanoptera: Melanthripidae) with a description of a new species from Argentina - de Borbón, Carlos Manuel (Zootaxa, 2009)
A new species of Melanthripidae, Dorythrips moundi, is described from Mendoza, Argentina, from the flowers of Zuccagnia punctata (Fabaceae). This species differs from the other members of Dorythrips because it lacks the cephalic projection previously considered characteristic of this genus. The genus is redefined and a key provided to the four genera of Melanthripidae worldwide, together with a key to the six species of Dorythrips. Two of these are from Western Australia and four from southern South America, with D. chilensis recorded from Argentina for the first time.